The impact of leadership on learner outcomes. A case of Bhangwe Cluster in Mberengwa District. - Ndlovu, Webster (Midlands State University, 2020)
The study sought to establish the impact of school leadership on learner outcomes. The idea behind carrying out the research was to make sure that solutions to rectify the problems faced by the cluster were found. The research was carried out in Mberengwa District. The researcher used the case study design to carry out the study. The study used questionnaires and interviews to collect data. In the study twenty teachers and five school Heads were used as research subjects. The research found that the problems that caused poor outcomes emanated from five behaviors by school leadership. The study found that lack of clinical supervision by school Heads, lack of staff development meetings on instructional leadership, not involving teachers in decision-making- process, not involving parents in school activities and unequal treatment of teachers by school Heads caused learners to perform badly in the cluster. The study recommends that the school Heads, teachers and parents should work together in order to alleviate the problems faced by learners in terminal examinations. This can be done by regular staff development meetings on instructional leadership by school Heads, clinical supervision by school Heads, involving teachers in decision-making process, treating teachers equally and involving parents in all the school activities.